Qualitative Examination of the Borax and Formalin Content in Food Ingredients and Snack Food - Sulistiyorini, Desy (PT. Riset Press International, 2024)
The misuse of formalin and borax remains prevalent, particularly in the processing and preservation of fish. Hence, the primary objective of this research was to ascertain the presence of formalin and borax in food specimens originating from the Depok and East Jakarta locality. The specimens utilized for this investigation encompassed white tofu, yellow tofu, wet noodles, salted snakeskin gourami, salted rainbow sardines, salted fish bulu ayam, salted rebon freshwater shrimp, salted squid, Indonesian style rice crackers (kerupuk gendar), frozen meatballs, and meatballs procured from vendors along the roadside. Qualitative assessments were conducted on the specimens utilizing the formalin test kit for formalin detection, while borax presence was determined through both turmeric extract and turmeric paper. The outcomes derived from this study revealed that samples of wet noodles, Indonesian style rice crackers, and salted rebon freshwater shrimp exhibited positive indications for borax, as evidenced by a discernible alteration in color to red-brownish. In terms of formalin content analysis, the findings demonstrated that yellow tofu, white tofu, wet noodles, and salted rebon freshwater shrimp samples tested positive for formalin using the formalin test kit reagent. It is recommended that regulatory authorities implement regular inspections to monitor the improper use of food additives, particularly preservatives that are prevalent within the community. Furthermore, the general populace is advised to exercise caution when selecting food items to ensure their safety.